Comportamento hidrológico em bacia hidrográfica da savana amazônica e cenários de usos do solo - Nobrega, Silvestre Lopes da (2018)
Amazon biome constitutes the biggest drainage network of the planet, with a vegetal physiognomy characterized for the predominance of forest and floodplains, it is responsible for 73,6% Brazilian water resources, and part of savanna located in the north region of Amazon and to the north and northeast of the state of Roraima, extending into the Guiana Shield and Gran Sabana. The savanna landscape has a complex characteristic for the study of hydric dynamics, due to uncertainties in the qualification of this natural resource and methodologies that need improvement to modelling the hydrologic response of the water sources against hydrodynamics and interaction with floodplains, isolated lakes, as well as change in use and occupation land in this savanna region. The main objective of this study was to contribute to the knowledge of the hydrologic response in the borders of Surumu river basin in an area of 12.664,14 km², where 77,7% are savanna, 21,5% forest, 1% agricultural use and 0,2% surface area covered by water, distributed in 71,4% modeled of dissection, 20,7% planation and 7,7% accumulation. The hydrological simulation with a discretization method composed by forms of modelling and use and occupation of the land provided a parameter approach a large-scale hydrological model, applied to many South American basins (MGB-IPH), to the concepts and physical characteristics through the interaction with the landscape concept, since the savannas and forests show distinct phytophysiognomies depending on the geomorphological environment. Savanna vegetation plays an important role in producing water and keeping minimum reference flows. Scenarios of replacement of 20 and 50% in the area of savanna vegetation by agricultural use in planation and accumulation modelling cause a slight increase in minimum, medium and maximum simulated flows, in most of the main Surumu river basin tributaries.